Personalized Pricing and Quality Differentiation - Choudhary, Vidyanand; Ghose, Anindya; Mukhopadhyay, Tridas; Rajan, Uday (Management Science, 2005)
We develop an analytical framework to investigate the competitive implications of personalized pricing (PP), whereby firms charge different prices to different consumers based on their willingness to pay. We embed PP in a model of vertical product differentiation and show how it affects firms’ choices over quality. We show that firms’ optimal pricing strategies with PP may be nonmonotonic in consumer valuations. When the PP firm has high quality, both firms raise their qualities relative to the uniform pricing case. Conversely, when the PP firm has low quality, both firms lower their qualities. Although many firms are trying to implement such pricing policies, we find that a higher-quality firm can actually be worse off with PP. While it is optimal for the firm adopting PP to increase product differentiation, the non-PP firm seeks to reduce differentiation by moving in closer in the quality space. While PP results in a wider market coverage, it also leads to aggravated price competition between firms. Because this entails a change in equilibrium qualities, the nature of the cost function determines whether firms gain or lose by implementing such PP policies. Despite the threat of first-degree price discrimination, we find that PP with competing firms can lead to an overall increase in consumer welfare.